2021
DOI: 10.1186/s13063-021-05161-4
|View full text |Cite
|
Sign up to set email alerts
|

Napping on the night shift and its impact on blood pressure and heart rate variability among emergency medical services workers: study protocol for a randomized crossover trial

Abstract: Background There is an emerging body of evidence that links exposure to shift work to cardiovascular disease (CVD). The risk of coronary events, such as myocardial infarction, is greater among night shift workers compared to day workers. There is reason to believe that repeated exposure to shift work, especially night shift work, creates alterations in normal circadian patterns of blood pressure (BP) and heart rate variability (HRV) and that these alterations contribute to increased risk of CVD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…Thirty‐six studies 16,22,56–89 were excluded because they did not investigate a 24‐h shift and 15 studies 90–104 did not have a continuous shift or had an unclear or undefined shift length. One study 105 was excluded because it did not compare the effect of shift work after 24 h. In addition, one study 106 was excluded because it was not available in the English language, three studies 107–109 used sleep as an experimental condition, and one study 110 was a letter to the editor. The excluded studies, with reasons for exclusion at full‐text screening, are described in Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty‐six studies 16,22,56–89 were excluded because they did not investigate a 24‐h shift and 15 studies 90–104 did not have a continuous shift or had an unclear or undefined shift length. One study 105 was excluded because it did not compare the effect of shift work after 24 h. In addition, one study 106 was excluded because it was not available in the English language, three studies 107–109 used sleep as an experimental condition, and one study 110 was a letter to the editor. The excluded studies, with reasons for exclusion at full‐text screening, are described in Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…We conducted a randomized crossover trial with participants assigned to three separate 72-hour conditions comprised of 36 hours of at-home monitoring (07:00–19:00 + 1 day), followed by a 12-hour in-lab night shift (19:00–07:00), 12-hour in-lab recovery opportunity (07:00–19:00), and 12-hour at-home recovery opportunity (19:00–07:00) ( 12 ). Two intervention conditions included a nap that began at 02:00 (30 minutes or 2 hours) during the simulated night shift.…”
Section: Methodsmentioning
confidence: 99%
“…Nap-specific measures were assessed immediately pre-nap and again at +0, +10, +20, and +30 minutes post-nap. Participants wore multiple non-invasive physiological devices throughout each condition (findings reported elsewhere) ( 12 , 20 ) and completed the Brief 3-minute version of the Psychomotor Vigilance Test (PVT-B) ( 21 ). The PVT-B measured reaction time [RT in milliseconds (ms)], lapses (RT>355ms), false starts (reactions before stimulus or RT<100ms), and speed (1000/RT) ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyang-Min et al found that mtDNA methylation in the blood of people exposed to PM 2.5 is negatively correlated with PM 2.5 concentration, and also found that the heart rate variability of subjects with higher mtDNA methylation levels is more likely to be affected by PM 2.5 [ 42 ]. As we all know, heart rate variability is a very valuable indicator for predicting sudden cardiac death and arrhythmia events, and can be used to determine the condition and prevention of CVD [ 43 ]. In recent years, some studies have begun to pay attention to the relationship between PM and heart rate variability to speculate on important risk factors for CVD [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%